CFD ANALYSIS OF BIFURCATED ARTERY WITH VARIABLE PARAMETERS - Muhammad Waheed Ashraf; Saqib Qamar; Ali Haider; Dilbar Hafeez; Muhammad Bader Munir; Muhammad Athar khan; Afnan ahmed (Spectrum of Engineering Sciences, 2025)
Cardiovascular disease (CVD) continues to be a top health concern worldwide, frequently developing when fat, cholesterol, calcium, fibrin and wastes collect on artery walls. If blockages remain untreated, they may result in heart attacks, strokes, hypertension and sudden cardiac death. The complex design of bifurcated arteries puts them at risk of both wrong flow and the formation of plaques. The goal of this study is to see how the angles at which arteries split influence blood movement within them using Computational Fluid Dynamics (CFD). It examines wall stress, velocity and pressure in the presence of both Newtonian and non-Newtonian pulsatile flow conditions. The bifurcated artery model was first developed with SolidWorks and then analyzed using Ansys Fluent to examine how the shape of the bifurcation (angles of 35°, 50°, 65° and 75°) influences wall shear stress, velocity and pressure. At the outset, simulations were carried out for steady-state situations, treating blood as Newtonian and applying the energy equation to keep body temperature at 37°C. Non-Newtonian behaviour was captured and blood’s ability to thin under shear stress was modelled, after which pulsatile flow was used to correctly represent the dynamic cycles of the heart. The results suggest that higher bifurcation angles are connected to lower wall shear stress, reduced blood flow, greater pressure and more flow disturbances. It becomes clear from pulsatile flow that the blood takes longer to accelerate and loses more energy as the angulation increases. Analysis using a mesh with sensitivity revealed that results are fully resolved at 0.1 mm or higher. The study points out the important effects of arterial walls and blood flow properties on blood circulation and gives useful information for improving cardiovascular tests, estimating disease development and planning better vascular treatment approaches.